Call s1= speed of

**riverboat**s2= speed of current We have system of linear equation: (1) (s1 + s2)*3=30...2 Answers · Science & Mathematics · 25/02/2013

d = rt let V km/h = rate of boat & v km/h that of stream, then (V+v)*3 = 30 or V+v = 10 (V-v)*5 = 30 or V-v = 6 adding, 2V = 16, V = 8 ans: 8 km/h ------

1 Answers · Science & Mathematics · 24/08/2011

Let speed of boat in still waters be x km / hour and speed of current be y km/ hour DOWNSTREAM ------------------------- SPEED = DISTANCE / TIME ( x+ y ) = 70/5 = 14 .............(A) UPSTREAM -------------------- SPEED...

2 Answers · Science & Mathematics · 27/04/2013

Speed of the boat in still water = u kph Speed of the water current = v kph Distance traveled = d = 30 km Time taken to travel downstream = t1 = 3 hr Time taken to travel upstream = t2 = 5 hr We have the following...

1 Answers · Science & Mathematics · 22/11/2013

b = speed of boat in still water c = speed of current (distance) = (rate)(time) 30 mi. = (b - c)(2.5 hr.) 12 mph = b - c [1] 30 mi. = (b + c)(2 hr.) 15 mph = b + c [2] [2] - [1]: 3 mph = 2c c = 1.5 mph [1] + [2]: 27 mph = 2b b = 13.5 mph

1 Answers · Science & Mathematics · 06/03/2010

The trip up the river has a speed of 72miles / 6 hours = 12mph. The trip ... c be the speed of the current and let b be the speed of the boat. The trip to St.Louis is going against the current. Thus...

1 Answers · Science & Mathematics · 31/08/2011

going up taking s as speed on still water and c as speed of current (s-c)*2.5=30 oing back (s+c)*2=30 2.5s-2.5c=30 2s+2c=30 2.5s+2.5c=37.5 -5c=-7.5 c=1.5 sub into the origonal equation (s-1.5)*2.5=30 s-1.5=30/2.5=12 s=12+1.5=13.5 2. taking A as the price of a ticket in section A and B as the price of...

1 Answers · Science & Mathematics · 07/06/2008

D = R * T Problem #1 ----------- Solving D=RT for time: T = D/R Time upriver = D/12 Time downriver = D/15 Time up + Time down = 7.5 D/12 + D/15 = 7.5 5D...

1 Answers · Science & Mathematics · 29/02/2008

eq 1: 3x - 2y = 0 eq2: x + 6y = 5 in eq 2 subtract 6y from each side x = 5 - 6y substitute this into eq 1: 3(5- 6y) - 2y = 0 multiply out: 3*5 - 3*6y -2y = 0 15 - 18y -2y = 0 collect terms: 15 - 20y = 0 subtract 15 from both sides -20y = -15y divide both sides by -20 y = -15 / - 20 do arithmetic y = 3/4 = 0...

1 Answers · Science & Mathematics · 05/06/2008

1 ))) let x = amount loaned at 9% simple interest ......y = amount loaned at 6% simple interest 9% x + 6% y = 810 0.09 x + 0.06 y = 810...............equation (1) x + y = 12,000 subtract y from both sides of the equation x = 12,000 - y............................equation (2) substitute the value of x in eq (2...

2 Answers · Science & Mathematics · 09/04/2011